2015
DOI: 10.4085/1062-6050-50.7.03
|View full text |Cite
|
Sign up to set email alerts
|

Kinesio Tape and Shoulder-Joint Position Sense

Abstract: . Ms Aarseth is now with Black Hills Surgical Hospital, Rapid City, SD.Context: Joint position sense (JPS) is a key neuromuscular factor for developing and maintaining control of muscles around a joint. It is important when performing specialized tasks, especially at the shoulder. No researchers have studied how Kinesio Tape (KT) application affects JPS.Objective: To investigate the effects of KT application and no tape on shoulder JPS at increasing shoulder elevations in athletes.Design: Cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 21 publications
2
36
2
1
Order By: Relevance
“…Similar results were found following the kinesio taping application in the athletic shoulder. Zanca et al 104 did not find changes in scapular kinematics in throwers after taping application, and Aarseth et al 105 showed that joint position sense get impaired after kinesio taping in healthy athletes. Furthermore, rigid taping does not seem to be beneficial to any of the outcomes assessed.…”
Section: Discussionmentioning
confidence: 98%
“…Similar results were found following the kinesio taping application in the athletic shoulder. Zanca et al 104 did not find changes in scapular kinematics in throwers after taping application, and Aarseth et al 105 showed that joint position sense get impaired after kinesio taping in healthy athletes. Furthermore, rigid taping does not seem to be beneficial to any of the outcomes assessed.…”
Section: Discussionmentioning
confidence: 98%
“…Although studies that tested the effectiveness of NEB on dysfunction in athletes present controversies, recent research has indicated positive effects in the short term period on reducing pain and increasing the ROM of the glenohumeral joint and cervical spine (10)(11)(12)(13)(14) , and improved performance in MTP&RehabJournal 2017, 15: 480 sports that require efforts with repetitive movement and high intensity characteristics (9,(15)(16)(17) . Additionally, the method is described as capable of generating improvement in local circulation, a reduction in edema, facilitation or relaxation of muscles, and improving joint position and proprioception due to optimization of the sensory mechanism (7)(8)18) , characteristics which contribute to improving athletic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The most common alterations found are the onset of pain, shoulder instability, scapular dyskinesia (1) , an increased range of motion (ROM) of external rotation and a reduction in ROM of internal rotation of the glenohumeral joint in the dominant shoulder performing the throwing gesture (5,6) . Recent investigations in handball athletes point to the need to carry out rehabilitation programs that aim to improve the instability of the glenohumeral joint, widely used in the various tasks of this modality (7,8) . Among the intervention methods aimed at minimizing instability, the neuromuscular elastic bandage (NEB) stands out, widely used in various areas of rehabilitation and especially in the sports community in various modalities (8,9) .…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical studies showed that KT may improve shoulder joint position sense (Aarseth et al, 2015) and round shoulders posture (Han et al, 2015) in healthy subjects. In addition, it may improve pain, scapular motion, muscle performance (Hsu et al, 2009) and health related quality of life (evaluated by DASH or SPADI scales) (Kaya et al, 2010;Simsek et al, 2013;Thelen et al, 2008) in patients with shoulder pain and impingement.…”
Section: Discussionmentioning
confidence: 99%